Another Reason for Non-neutrality of Financial Liquidity - Lee, Jong-Eun (Panoeconomicus, 2018)
This paper reinterprets the non-neutrality of financial liquidity under a general equilibrium model with multiple financial liquidities, but without price stickiness. Non-neutrality opens the possibility of effective monetary or financial policy on the crisis-prone real economy and thus revisiting its nature is worthwhile. We find that models with only one asset and money limit our perspectives to see the nature of financial liquidities interacting with real economy. Departing from abstracting an economy with only one interest rate allows us to see the underlying reason of non-neutrality of financial liquidities, that is, industry-specific rates of return distinguishable from the representative rate of return. Without the assumption of price stickiness but with a wider frame of multiple liquidities, this paper offers another reason for non-neutrality of financial liquidity and naturally clarifies the meaning of money neutrality. We incorporate complicated reality of multiple financial liquidities in a theoretical model, which is a way of deepening our understanding of the nature of the financial market. Key words: financial liquidity, non-neutrality, dichotomy.JEL: E44, E51.Još jedan razlog za ne-neutralnost finansijske likvidnostiU radu je reinterpretirana ne-neutralnost finansijske likvidnosti u okviru modela opšte ravnoteže sa višestrukim finansijskim likvidnostima, ali bez lepljivih cena. Ne-neutralnost otvara mogućnost efektivne monetarne ili finansijske politike u realnoj ekonomiji podložnoj krizama, te je na taj način ponovno razmatranje njene prirode korisno. Smatramo da modeli sa samo jednom imovinom i novcem ograničavaju našu perspektivu u razumevanju prirode finansijskih likvidnosti u interakciji sa realnom ekonomijom. Polazeći od apstrahovanja ekonomije sa samo jednom kamatnom stopom, možemo da uočimo osnovni razlog ne-neutralnosti finansijskih likvidnosti, odnosno, specifične industrijske stope prinosa koje se razlikuju od reprezentativne stope prinosa. Bez pretpostavke o lepljivosti cena, ali sa širim okvirom višestrukih likvidnosti, ovaj rad nudi još jedan razlog u korist ne-neutralnosti finansijske likvidnosti i prirodno pojašnjava značenje neutralnosti novca. U teorijski model inkorporiramo kompleksnu realnost višestrukih finansijskih likvidnosti, što predstavlja način da se produbi naše razumevanje finansijskog tržišta.Ključne reči: Finansijska likvidnost, ne-neutralnost, dihotomija.